KESETARAAN GENDER SEBAGAI PEMENUHAN KONSTITUSI - Sodik, Mochamad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
The drafting of the Draft Law on Gender Equality has brought criticism, many of which based on reactionary-ideological grounds unsuitable to productive discussion, and it is indeed regrettable that such responses against the draft law were not made in an academic framework and in accordance with the principle of proportionality. In a democratic state, gender equality is a fundamental part rooted deeply in human rights, similar to racial, ethnic, class, special-needs and religious equality. Thus as a democratic nation state, Indonesia is obliged to fulfill the basic rights of each of its citizens without regard to origin or gender. Such rights encompass a variety of aspects: the right to life, security, health, education, economic, political and socio-cultural rights. All basic rights must be fulfilled equally to avoid discrimination. Thus, normatively, the 1945 Constitution of the Republic of Indonesia has guaranteed equality of all citizens, whether male or female. In a global context, Indonesia has also ratified the CEDAW (Convention on the Elimination of all forms of Discrimination Against Women) through Law No. 7 of 1984. Indonesia’s commitment to improve gender equality is also written down in the MDGs (Millennium Development Goals). Therefore, through a philosophical-juridical-sociological viewpoint, gender equality (enshrined in law) is both a constitutional mandate and a contemporary demand